2012
DOI: 10.1176/appi.ap.10060085
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Professional Role Competency During Psychiatry Residency

Abstract: On the basis of this needs assessment and the Royal College recommendations, MSF may be considered a potential assessment tool for evaluating psychiatry residents in their professional role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 8 publications
0
0
1
Order By: Relevance
“…To our knowledge, this is the first study exploring and comparing learning needs, preferences and career attitudes of IPRs grouped according to different geographic areas. In this survey, the response rate for residents was 34%, slightly lower compared to what previous international studies in the field reported, ranging from 40.5% to 86% [14, 18, 20, 23, 24]. This response rate might be due to several factors, such as the (only) recent launch of the SOPSI-GG section, with a limited power to reach residents and poor attitude to research on this topic in Italy.…”
Section: Discussioncontrasting
confidence: 63%
“…To our knowledge, this is the first study exploring and comparing learning needs, preferences and career attitudes of IPRs grouped according to different geographic areas. In this survey, the response rate for residents was 34%, slightly lower compared to what previous international studies in the field reported, ranging from 40.5% to 86% [14, 18, 20, 23, 24]. This response rate might be due to several factors, such as the (only) recent launch of the SOPSI-GG section, with a limited power to reach residents and poor attitude to research on this topic in Italy.…”
Section: Discussioncontrasting
confidence: 63%